Effect of Crystal Phase of MnO2 with Similar Nanorod‐Shaped Morphology on the Catalytic Performance of Benzene Combustion. Issue 2 (11th January 2019) - Hu, Zhun; Mi, Rongli; Yong, Xiang; Liu, Shuang; Li, Dan; Li, Yu; Zhang, Tao
Abstract: Four manganese oxides with different crystal structures in the similar nanorod‐shaped morphology were synthesized and investigated for the catalytic combustion of benzene. The physicochemical properties of the materials were characterized by N2 physisorption‐desorption, transmission electron microscope (TEM), X‐ray photoelectron spectroscopy (XPS), Raman spectra, O2 temperature programmed desorption (O2 ‐TPD) and temperature programmed surface reaction (TPSR). The catalytic activities on benzene combustion over various manganese oxides decreased in the order: γ‐MnO2 > β‐MnO2 > α‐MnO2 > δ‐MnO2 . The activation energy of benzene combustion over γ‐MnO2 (67.4 kJ/mol) was lower than that over α‐MnO2 (69.2 kJ/mol), β‐MnO2 (79.1 kJ/mol) and δ‐MnO2 (85.2 kJ/mol). The TPSR results with or without gaseous oxygen revealed that the reaction pathway was occurred via MVK mechanism. The surface adsorbed oxygen species concentration and low temperature O2 desorption of these manganese oxides, determined by XPS and O2 ‐TPD, decreased in the order of γ‐MnO2 > β‐MnO2 > α‐MnO2 > δ‐MnO2, are in good agreement with the sequence of their catalytic performance on benzene combustion. It is concluded that higher surface adsorbed oxygen species ratio and better low temperature O2 desorption were crucial to the superior catalytic performance of the α‐MnO2, β‐MnO2, γ‐MnO2 and δ‐MnO2 materials. Abstract : α‐, β‐, γ‐, and δ‐MnO2 with similar nanorod‐shaped were synthesized to investigate the effect of different MnO2 crystalline form on catalytic performance of benzene combustion. γ‐MnO2 exhibited superior catalytic activity which could be attributed with the adsorbed oxygen concentration and oxygen mobility over MnO2 catalyst.